2023
DOI: 10.1158/2159-8290.22530965.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplementary Figures S1 - S6 from Bruton Tyrosine Kinase–Dependent Immune Cell Cross-talk Drives Pancreas Cancer

Abstract: <p>Supplementary Figure S1. B cells in human PDAC. Supplementary Figure S2. B cells and FcRgamma-positive cells regulate murine PDAC. Supplementary Figure S3. Leukocytes and BTK in human and murine PDAC. Supplementary Figure S4. Macrophage PI3Kgamma activates BTK to promote PDAC progression. Supplementary Figure S5. BTK and PI3Kgamma-inhibition decrease PDAC growth. Supplementary Figure S6. BTK inhibition improves gemcitabine response in late-stage PDAC.</p>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The clinical role of BTK extends beyond its effects on normal and malignant B cells. PI3Kg can activate BTK to promote phospholipase C (PLC) g-dependent signaling in hematopoietic cells, including myeloid cells (69). A recent study suggested a regulatory role for BTK in T-cell activation.…”
Section: Btk Inhibitors (Btki)mentioning
confidence: 99%
“…The clinical role of BTK extends beyond its effects on normal and malignant B cells. PI3Kg can activate BTK to promote phospholipase C (PLC) g-dependent signaling in hematopoietic cells, including myeloid cells (69). A recent study suggested a regulatory role for BTK in T-cell activation.…”
Section: Btk Inhibitors (Btki)mentioning
confidence: 99%